Beer volatile fingerprinting at different brewing steps - Alves, Vera (2021)
Volatile fingerprints of a lager beer were carried out throughout five brewing steps to characterize the changes encompassing this process. Overall, 60 volatile organic metabolites (VOMs) were identified by headspace solid phase microextraction followed by gas chromatography mass spectrometry (HS-SPME/GC–MS). Specific profiles were observed at different brewing steps - aldehydes and furans dominate in wort, whereas the aliphatic esters and alcohols predominate in the following steps. Such variations can be assigned to specific VOMs, as 3-me thylbutanal (wort), ethyl alcohol and ethyl octanoate (fermentation, maturation and filtration), or ethyl alcohol and isoamyl acetate (final product). These VOMs can influence the beer final flavour. Ethyl alcohol contributes to its strong and pungent smell and taste, while isoamyl acetate adds intense ‘fruity’ and ‘banana’ odours. These beer volatile fingerprints constitute a valuable tool to obtain insights on the impact of each brewing step on the final product, being also very useful for certification purposes.